Pedagogical Psychology: Beyond the 21st Century - Gretchen M Reevy (Frontiers Research Topics, 2015)
Frontiers in Psychology is introducing a new research topic, Pedagogical Psychology: Beyond the 21st Century, which will be released as an online journal issue in summer 2014. The purpose of Beyond the 21st Century will be to publish goal- oriented articles leading to improvement of teaching and learning at all levels of psychology education. Until perhaps 20 years ago, educational approaches to teaching were largely informed by a "Stand and Deliver" pedagogical attitude. The psychology of this approach has often invested unrealistic and unrealizable responsibilities in both teachers and students. With the emergence of electronic data sharing (e.g., the Internet) and global cooperation/competition, newer approaches to teaching have begun to supplement and sometimes replace the older model of teaching. These newer approaches have simultaneously taken advantage of technological advances, global changes, and an evolving understanding of successful student-mentor relationships. As the pedagogical models driven by these changes evolve into the 22nd century and beyond, what seems groundbreaking today will, in hindsight, be seen as hidebound. Thus, the major goal of Beyond the 21st Century will be to publish manuscripts which imaginatively, but realistically anticipate future trends in teaching undergraduate psychology.